Enabling Smart City With Intelligent Congestion Control Using Hops With a Hybrid Computational Approach. (3rd July 2020) - Abbas, Sagheer; Khan, Muhammad Adnan; Athar, Atifa; Shan, Syed Ali; Saeed, Anwar; Alyas, Tahir
ABSTRACT: In a smart city, the subject of the congestion-free traffic has been leading objectives from the past decade, and many approaches are adopted to make congestion-free roads. These approaches and signals at one junction are not inter-linked with the signal at the previous one. Therefore, the traffic flow on the same road and at associative roads is not smooth. The study proposed a model with a hybrid computational approach in which the current signal incorporates the associative signals information. Simulation results have shown that the proposed approach gives more attractive results as compared to previously published approaches. It will help improve the flow of traffic and reduce traffic congestion.